2013
DOI: 10.1016/j.sapharm.2012.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Requests for emergency contraception in community pharmacy: An evaluation of services provided to mystery patients

Abstract: Ongoing training is required to enhance the skills, competence, and confidence of pharmacy staff in managing complicated requests for nonprescription medicines, such as the ECP. The impact of time pressures and financial burdens on the provision of pharmaceutical services needs to be acknowledged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…This figure is consistent with previous studies in this population looking at appropriate supply of non-prescription medication, where a written checklist was not used in practice 6,9. The finding of variable practice is also similar to other research assessing EC supply in Australia using similar methodology 7,10…”
Section: Discussionsupporting
confidence: 90%
“…This figure is consistent with previous studies in this population looking at appropriate supply of non-prescription medication, where a written checklist was not used in practice 6,9. The finding of variable practice is also similar to other research assessing EC supply in Australia using similar methodology 7,10…”
Section: Discussionsupporting
confidence: 90%
“…A number of studies have focused on pharmacy privacy and the provision of emergency hormonal contraceptives (the ‘morning‐after pill’). A ‘mystery shopper’ Australian study reported low use of private and semi‐private consultation areas . Other emergency hormonal contraceptive studies similarly highlighted concerns around lack of pharmacy privacy …”
Section: Introductionmentioning
confidence: 99%
“…Practising pharmacists are often confronted with ethically challenging scenarios which require consideration of legal and ethical boundaries, and the application of professional judgement. Pharmacists may find it difficult to apply ethical reasoning skills in practice, especially in relation to more complicated issues such as the supply of EHC . It is therefore important to equip pharmacy students with the knowledge and skills to behave ethically.…”
Section: Discussionmentioning
confidence: 99%